Historical Roots of International Biomedical and Health Informatics: The Road to IFIP-TC4 and IMIA through Cybernetic Medicine and the Elsinore Meetings - Kulikowski, C. A. (Yearbook of Medical Informatics, 2017)
Background: It is 50 years since the International Federation of Information Processing (IFIP) Societies approved the formation of a new Technical Committee (TC) 4 on Medical Information Processing under the leadership of Professor Francois Grémy, which was the direct precursor of the International Medical Informatics Association (IMIA).Objectives: The goals of this paper are to give a very brief overview of early international developments leading to informatics in medicine, with the origins of the applications of computers to medicine in the USA and Europe, and two meetings - of the International Society of Cybernetic Medicine, and the Elsinore Meetings on Hospital Information Systems - that took place in 1966. These set the stage for the formation of IFIP-TC4 the following year, with later sponsorship of the first MEDINFO in 1974, setting the path for the evolution to IMIA.Methods: This paper reviews and analyzes some of the earliest research and publications, together with two critical contrasting meetings in 1966 involving international activities in what evolved into biomedical and health informatics in terms of their probable influence on the formation of IFIP-TC4.Conclusion: The formation of IFIP-TC 4 in 1967 by Francois Grémy arose out of his concerns for merging, at an international level, the diverse strands from the more abstract work on cybernetic medicine and its basis in biophysical and neural modeling, with the more concrete and health-oriented medical information processing that was developing at the time for hospitals and clinical decision-making.
Keywords: International Biomedical and Health Informatics; IFIP-TC4; History; Cybernetic Medicine; Elsinore Meetings; IMIA; François Grémy